PERFORMANCE OF CASTOR BEAN SELECT UNDER SALINE IRRIGATION WATER - & et al., Elsahookie (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
To determine the influence of selection on castor bean (Ricinus communis cv. Hindi 21) grown on a saline sodic soil, two experiments were conducted in 2011 and 2012. The first experiment was applied on the Farm of College of Agric./Univ. of Baghdad. It involved planting castor bean in three methods in saline-sodic soil. The second experiment was applied by planting the original cultivar and the new select. Three levels of irrigation water salinity were used; 1.5, 6, and 12 dS.m1. However, plants of higher salinity did not grow normal, so they were discarded. The results revealed that the new select outyielded the original when it gave 174.3 g plant seed yield. This select characterized by heavier seed weight (0.24 g/seed), higher number of each of seed/plant (724) and plant fruiting racemes (12.7).When irrigating with 6 dS.m-1 saline water, it gave 188.7 g plant seed yield, 0.26g.seed-1, and 11.7 raceme.plant-1. However, the best genetic/environmental variance ratio were with plant seed number, total dry matter, and crop gowth rate. This indicate the validity of using these traits when selecting for abiotic stress tolerance due to their high heritabilities. It was suggested that re-selection on same selected plants tolerant to salinity would bring more QTLs of abiotic stress to the new select. Selecting on large population under several salinity levels will give better results. Covering selected tolerant plants with muslin cloth bags will tend to increase selfing.